COMPARATIVE ANATOMICAL , HISTOLOGICAL AND HISTOCHEMICAL STUDY OF (LARYNX, TRACHEA AND SYRINX) BETWEEN MATURE AND IMMATURE MALES OF LOCAL DUCK (Anas Platyrhnchos ) - Ansam AL- Ahmed; Alaa Sadoon (Basrah Journal of Veterinary Research)
The present study aims to compare gross anatomical, histological andhistochemical structures of the larynx, trachea and syrinx between mature(Drake) andimmature (Duckling) male duck(Anas platyrinchous ) . Twelve healthy local malesducks were divided into two groups. Six Drake at one year old and six Duckling atthree months .For anatomical study the larynx, trachea and syrinx were measured byusing vernia . For histological study specimens from larynx, trachea and syrinx werefixed in 10% formaldehyde after that the specimens embedded in paraffin. The next steptissues were sectioned using microtome and stained with routine stain and special stains.The anatomical results revealed that larynx, syrinx and trachea are identical in positionin both Drake and Duckling , but differ in size . The histological results revealed thatlarynx of both Drake and Duckling lined by keratinized pseudostratified squamousepithelial tissue that appears thicker in Drake than Duckling . Trachea of Drake andDuckling lined with ciliated pseudostratifed columnar epithelial with mucous glands ,supported by ossified cartilages in Drake and hyaline cartilage in Duckling . Syrinx ofboth Drake and Duckling lining by the ciliated pseudostratifed columnar epithelial withfew goblet cells. Beneath it the lamina properia and sub mucosa that contained in looseconnective tissue with blood vessels and amount of elastic and collagen fibers beneathit in Drake spongy bone trabeculae that contains bone lacuna fills with osteocytes ,while in Duckling hyaline cartilage . The hyaline cartilage consists of lacuna whichcontains chondrocytes.